2013
DOI: 10.1159/000353667
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Open-Label, Controlled Study Comparing the Efficacy, Safety and Cost-Effectiveness of a Sequential Therapy with RV4104A Ointment, Ciclopiroxolamine Cream and Ciclopirox Film-Forming Solution with Amorolfine Nail Lacquer Alone in Dermatophytic Onychomycosis

Abstract: Background: The efficacy of topical antifungals is controversial. Objective: To compare the efficacy and safety of a sequential (SEQ) treatment with chemical nail avulsion and topical antifungals to amorolfine nail lacquer in dermatophytic onychomycosis. Methods: This was a randomized, parallel-group, controlled study comparing a 36-week SEQ treatment with chemical nail avulsion with RV4104A ointment (class I medical device containing 40% urea) followed by ciclopirox cream for 8 weeks and ciclopirox nail lacqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…However, in the present trial, the efficacy of amorolfine 5% nail lacquer (with a complete cure rate of about 12%) is higher than the results given in the study of Elewski et al [14] (where the complete cure rate was 0.96%) and substantially in line with the data obtained in the study of Paul et al [13] (12.7%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, in the present trial, the efficacy of amorolfine 5% nail lacquer (with a complete cure rate of about 12%) is higher than the results given in the study of Elewski et al [14] (where the complete cure rate was 0.96%) and substantially in line with the data obtained in the study of Paul et al [13] (12.7%).…”
Section: Discussionsupporting
confidence: 81%
“…In a recent multicenter, randomized, open-label and controlled study conducted on 142 onychomycotic patients, amorolfine 5% showed complete cure in 12.7% [13] .…”
mentioning
confidence: 99%
“…4e5, it can be seen that much of the lacquer film (and hence drug) is lost from the nail plate within 3e4 days of application. This could be partly responsible for the relatively low success rate of Curanail in the treatment of onychomycosis; a recent study reported a complete cure rate of only 13% in 71 patients with toenail onychomycosis who applied amorolfine lacquer twice weekly for a period of 36 weeks [24]. Daily (rather than weekly) application or reformulation of this lacquer to improve its residence on the nail, such that a drugloaded film is present on the nail plate surface, especially on the fungally-infected parts, at all times, is therefore likely to improve its success rate in the topical treatment of onychomycosis.…”
Section: In Vivo Residence Of the Lacquers On The Fingernailmentioning
confidence: 99%
“…Oral therapy carries the inherent disadvantages of systemic adverse effects, drug interactions and contraindications, and is subject to a failure rate of 20%, as well as a relapse rate of 25% (Gupta, 2012;Roberts, 1999). Topical therapy, on the other hand, has a low success rate with currently available medicines, for example, 13-54% complete cure rates from amorolfine nail lacquer (Lauharanta, 1992;Paul et al, 2013;Reinel and Clarke, 1992), similarly low cure rates from ciclopirox nail lacquer (Gupta and Joseph, 2000), under 20% complete cure rate of efinaconazole solution (Tosti, 2013) and under 30% cure rate of tavaborole solution (Markham, 2014). Nail psoriasis affects approximately 1% of the population (Reich, 2009) and its treatment may involve repeated injections of corticosteroids into the nail folds, injections of biological agents such as adalimumab, photochemotherapy, topical or systemic treatment depending on the symptoms (Oram and Akkaya, 2013).…”
Section: Introductionmentioning
confidence: 99%